2011
DOI: 10.1021/jf1045969
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Antioxidant Activity of Lycopene (Z)-Isomers in Different Assays

Abstract: Several studies have implicated the potent antioxidant properties of lycopene. However, most of the studies used only the (all-E)-isomer. (Z)-Isomers of lycopene were found in substantial amounts in processed foods and in human tissues. In the present study, we investigated in vitro the antioxidant activity of (5Z)-, (9Z)-, and (13Z)-lycopene compared to the (all-E)-isomer. Additionally, prolycopene, the (7Z,9Z,7'Z,9'Z)-isomer found in tangerine tomatoes, was analyzed. No significant differences were found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 42 publications
4
123
0
Order By: Relevance
“…Based on the prevalence of lycopene cis isomers in plasma and tissues [23], emerging evidence suggesting their greater antioxidant potential than trans lycopene [36], and their hypothesized role as a preferred substrate for beta-carotene 9′,10′ dioxygenase 2 (BCDO2; an enzyme responsible for eccentric cleavage of carotenoids, discussed later) [37], future investigations should seek to describe the metabolism of cis versus trans lycopene. Based on the heterogeneity observed in these limited studies, this area of research could benefit from larger sample sizes, the use of isotopically-labeled tracer lycopene, and accounting for relevant genetic variation.…”
Section: Human Blood Lycopene Pharmacokineticsmentioning
confidence: 99%
“…Based on the prevalence of lycopene cis isomers in plasma and tissues [23], emerging evidence suggesting their greater antioxidant potential than trans lycopene [36], and their hypothesized role as a preferred substrate for beta-carotene 9′,10′ dioxygenase 2 (BCDO2; an enzyme responsible for eccentric cleavage of carotenoids, discussed later) [37], future investigations should seek to describe the metabolism of cis versus trans lycopene. Based on the heterogeneity observed in these limited studies, this area of research could benefit from larger sample sizes, the use of isotopically-labeled tracer lycopene, and accounting for relevant genetic variation.…”
Section: Human Blood Lycopene Pharmacokineticsmentioning
confidence: 99%
“…Lycopene and others carotenoids have been shown to act as prooxidants or antioxidants, depending on the dose at which they are administered. Many studies have reported the antioxidant effect of lycopene both in vivo (Sahin et al 2006) and in vitro (Shi et al 2007;Mu¨ller et al 2011), although the dose-dependent pro-oxidant effect has only been shown in vitro (Lowe et al 1999;Yeh and Hu 2000). It has been demonstrated that supplemented beta-carotene and other carotenoids are oxidatively degraded under heavy oxidative stress, which leads to the formation of high amounts of breakdown products with pro-oxidant properties (Siems et al 2005).…”
mentioning
confidence: 99%
“…(all-E)-Lycopene dispersed in POPC/cholate micelles exhibited an antioxidant power around 11 times higher than Trolox (TEAC ¼ 10.8). A lower antioxidant capacity of (all-E)-lycopene (a-TEAC ¼ 4) was recently reported by Muller et al, 46 who employed a two-phase water-n-hexane ABTSc + decolourization assay, analogue to that one adopted for LRO analysis. However these authors read the decolourization 2 min aer lycopene/ABTS mixing, thus determining a "fast" a-TEAC value.…”
Section: Antioxidant Activity Assessmentmentioning
confidence: 83%